Primary HPV and Molecular Cervical Cancer Screening in US Women Living With Human Immunodeficiency Virus. (3rd September 2020) - Strickler, Howard D; Keller, Marla J; Hessol, Nancy A; Eltoum, Isam-Eldin; Einstein, Mark H; Castle, Philip E; Massad, L Stewart; Flowers, Lisa; Rahangdale, Lisa; Atrio, Jessica M; Ramirez, Catalina; Minkoff, Howard; et al.
Abstract: Background: Primary human papillomavirus (HPV) screening ( PHS ) utilizes oncogenic human papillomavirus (oncHPV) testing as the initial cervical cancer screening method and typically, if positive, additional reflex-triage (eg, HPV16/18-genotyping, Pap testing). While US guidelines support PHS usage in the general population, PHS has been little studied in women living with HIV (WLWH). Methods: We enrolled n = 865 WLWH (323 from the Women's Interagency HIV Study [WIHS] and 542 from WIHS-affiliated colposcopy clinics). All participants underwent Pap and oncHPV testing, including HPV16/18-genotyping. WIHS WLWH who tested oncHPV[+] or had cytologic atypical squamous cells of undetermined significance or worse (ASC-US+) underwent colposcopy, as did a random 21% of WLWH who were oncHPV[−]/Pap[−] (controls). Most participants additionally underwent p16/Ki-67 immunocytochemistry. Results: Mean age was 46 years, median CD4 was 592 cells/µL, 95% used antiretroviral therapy. Seventy WLWH had histologically-determined cervical intraepithelial neoplasia grade 2 or greater (CIN-2+), of which 33 were defined as precancer (ie, [i] CIN-3+ or [ii] CIN-2 if concurrent with cytologic high grade squamous intraepithelial lesions [HSILs]). PHS had 87% sensitivity (Se) for precancer, 9% positive predictive value (PPV), and a 35% colposcopy referral rate (Colpo). " PHS with reflex HPV16/18-genotyping and Pap testing " had 84% Se, 16% PPV, 30% Colpo. PHS with only HPV16/18-genotyping had 24% Colpo. " Concurrent oncHPV and Pap Testing" (Co-Testing) had 91% Se, 12% PPV, 40% Colpo. p16/Ki-67 immunochemistry had the highest PPV, 20%, but 13% specimen inadequacy. Conclusions: PHS with reflex HPV16/18-genotyping had fewer unnecessary colposcopies and (if confirmed) could be a potential alternative to Co-Testing in WLWH. Abstract : Primary Human Papillomavirus (HPV) Screening ( PHS ) with reflex HPV16/18-genotyping resulted in fewer unnecessary colposcopies than HPV/Pap Co-Testing in Human Immunodeficiency Virus[+] women and had a high negative predictive value. PHS with HPV16/18-genotyping q3-5 years may be a potential alternative to Co-Testing in HIV[+] women.